2020
DOI: 10.1063/5.0011908
|View full text |Cite
|
Sign up to set email alerts
|

Microfluidic enrichment of bacteria coupled to contact-free lysis on a magnetic polymer surface for downstream molecular detection

Abstract: We report on a microsystem that couples high-throughput bacterial immunomagnetic capture to contact-free cell lysis using an alternating current magnetic field (AMF) to enable downstream molecular characterization of bacterial nucleic acids. Traditional methods for cell lysis rely on either dilutive chemical methods, expensive biological reagents, or imprecise physical methods. We present a microchip with a magnetic polymer substrate (Mag-Polymer microchip), which enables highly controlled, on-chip heating of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…The device could effectively lyse mammalian and bacteria cells, but it does not rupture the cell walls of some intractable microorganisms, according to the results. Burklund et al demonstrated a microfluidic device, which enabled highly controlled, on-chip heating for the lysis of bacteria cells [ 98 ]. The presented chip utilized an AC external magnetic field (AMF).…”
Section: Cell Lysis Methodsmentioning
confidence: 99%
“…The device could effectively lyse mammalian and bacteria cells, but it does not rupture the cell walls of some intractable microorganisms, according to the results. Burklund et al demonstrated a microfluidic device, which enabled highly controlled, on-chip heating for the lysis of bacteria cells [ 98 ]. The presented chip utilized an AC external magnetic field (AMF).…”
Section: Cell Lysis Methodsmentioning
confidence: 99%
“…Hedde et al also showed how 3D particle sorting enables the detection and isolation of E. coli from whole blood within minutes for clinically relevant fluid volumes (1-10 mL) [92]. Other combinations of microsystems coupling high throughput bacterial immunomagnetic capture to non-contact cell lysis using an alternating current magnetic field allow bacterial detection in the range of 10 2 CFU/mL with a flow rate of 50 mL/h [95].…”
Section: Microdroplets and 3d Particle Countermentioning
confidence: 99%
“…The limitation of magnetic nanoparticles is their slow response to external magnetic stimuli, which means that they need to form larger magnetic complexes by using high nanoparticle concentrations or have long incubation times (Burklund et al, 2020). Poncelet et al (2021) Frontiers in Bioengineering and Biotechnology frontiersin.org concentration was 10 3 CFU/ml in environmental water samples.…”
Section: Loading the Samplementioning
confidence: 99%